(untitled) - Pytel, Andrew (New York, 1994)
Introduction to statics, fundamental properties of vectors, representation of vectors using rectangular components, vector multiplication, ...
Keywords: Cơ học ứng dụng,Mechanics, Applied; Giáo trình,Textbooks